METHOD DEVELOPMENT AND VALIDATION OF A HIGHLY SELECTIVE AND SPECIFIC POSITIVE POLARITY ESI-LC-MS/MS METHOD FOR SIMULTANEOUS DETERMINATION OF SEMAGLUTIDE AND CANAGLIFLOZIN IN HUMAN PLASMA - VATSAVAYI, JAGAPATHI RAJU; REVU, NALANDA BABY (International Journal of Applied Pharmaceutics, 2025)
Objective: To develop a method capable of simultaneous estimation and quantification of semaglutide and canagliflozin being studied as a potential combination therapy for treating Diabetes. Materials: An elaborate protein precipitation extraction technique used verapamil as internal standards for semaglutide and canagliflozin. The two compounds were separated on a Zorbax C18 (50 mm x 2.1 mm, 5 µ Particle size) column, with a positive polarity Electro Spray Ionization (ESI) on a Liquid chromatograph with Tandem Mass Spectrometry (LC-MS/MS) instrument. The estimation was through a Multiple Reaction Monitoring (MRM) method, and a gradient program utilizing Acetonitrile and 5 mmol Ammonium formate with 0.1% formic acid as mobile phases to achieve a separation in 2.5 min. Results: The method established was performing linearly over a working range of 1.00 to 1000 ng/ml for both semaglutide (r2>0.98) and canagliflozin (r2>0.98) in human plasma. The specificity, selectivity, precision, accuracy, recovery, matrix effects and stability were within acceptable limits. The stability was established under various conditions as necessitated by the guideline on Bioanalytical method validation as mentioned in International Council for Harmonisation of Technical Requirements of Pharmaceuticals for Human Use (ICH) M10. Conclusion: This highly selective and sensitive method where 1.00 ng/ml was employed for semaglutide and canagliflozin as the Lower Limit of Quantification (LLOQ) can be utilized for estimation in human plasma will facilitate the further application to pharmacokinetic, bioequivalence and population pharmacokinetics studies for combination of these two drugs in pharmaceutical dosage forms.